2023
DOI: 10.1186/s12871-023-02170-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra-operative administration of subanesthetic s-ketamine on emergence from sevoflurane anesthesia: a randomized double-blind placebo-controlled study

Abstract: Background Ketamine is administered in the perioperative period for its benefits in analgesia, anti-agitation and anti-depression when administered at a small dose. However, it is not clear whether the intra-operative administration of ketamine would affect emergence under sevoflurane anesthesia. To investigate this effect, we designed this trial. Methods In this randomized, double-blind, placebo-controlled study, we enrolled 44 female patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Liu et al reported that on the background of sevoflurane anesthesia, a small dose of esketamine (0.125 mg/kg) induced active EEG spectra with decreased power of slow wave, delta, and alpha and increased power of beta-gamma in the prefrontal lobe. 34 The BIS, as an EEG derivative, is mainly a measure of prefrontal cortical electrical activity rather than the degree of consciousness. Thus, this active EEG pattern may account for the increased BIS values after continuous esketamine infusion in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that on the background of sevoflurane anesthesia, a small dose of esketamine (0.125 mg/kg) induced active EEG spectra with decreased power of slow wave, delta, and alpha and increased power of beta-gamma in the prefrontal lobe. 34 The BIS, as an EEG derivative, is mainly a measure of prefrontal cortical electrical activity rather than the degree of consciousness. Thus, this active EEG pattern may account for the increased BIS values after continuous esketamine infusion in our study.…”
Section: Discussionmentioning
confidence: 99%